Coming out - Steel, Danielle (New York : Dell Book, 2007)
Chaos erupts in the Rubinstein household when Olympia's twin daughters are invited to New York's most exclusive debutante ball--with one twin and Olympia's current husband refusing to attend, and the other young woman and Olympia's snobbish ex-husband already shopping for the event.
Booklist
Booklist, May 2006
Adult.
Adult
Keywords: Debutante balls -- Fiction; Debutantes -- Fiction; Balls (Parties) -- Fiction; Debutantes -- Fiction; Domestic fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Fiction; Domestic fiction